Evaluating urban wildlife management actions: an exploration of antecedent cognitive variables - Whittaker, Doug, author; Vaske, Jerry, advisor; Donnelly, Maureen, committee member; Knight, Richard, committee member; Manfredo, Michael J., committee member (Colorado State University. Libraries, 2000)
Addressing urban wildlife conflicts has become a wildlife management priority, but public acceptability can limit choices among conflict prevention and response actions. Theoretically based survey research is crucial to understanding public acceptability and the development of consensus solutions. The dissertation presents three papers that explore relationships between the acceptability of urban wildlife management actions and antecedent cognitive variables. Data come from a 1996-97 mail survey of 971 Anchorage, Alaska residents focused on moose, bear, and geese management issues. Applying a "cognitive hierarchy" framework, the papers use descriptive statistics, confirmatory factor analyses, and structural equation modeling to measure and link cognitive variables. The first paper compares beliefs and evaluations of possible hunt outcomes among those for and against an urban moose hunt, showing divergence in beliefs among the two groups. Belief differences suggest some opportunities for consensus decision-making, while also suggesting that certain conflicting beliefs are value-based and may be relatively resistant to change. The second paper examines the value-basis of acceptability for several wildlife management actions, including population-level prevention actions (e.g., hunts) and post-conflict response actions (e.g., killing individual animals involved in conflicts). Results suggest that patterns of basic wildlife beliefs align on two distinct value orientations (use-protection and wildlife appreciation), and these differentially predict action acceptability. Results also show stronger relationships with general acceptability for classes of actions or across several conflict situations, consistent with the cognitive hierarchy model. The final paper relates the acceptability of a moose hunt to both wildlife value orientations and "condition evaluations" (assessments of current moose population levels, winter sightings in neighborhoods, moose-vehicle accidents, and landscape damage incidents). Results show that population evaluations fully mediate condition evaluations and acceptability, but only partially mediate value orientations and acceptability. The model supports the cognitive hierarchy concept, but indicates that use-protection value orientations may overshadow the influence of intermediate condition evaluations. Linking chapters expand on the conceptual framework (the cognitive hierarchy, wildlife value orientations, and alternative research traditions for measuring evaluations) and discuss implications for future research and planning efforts. Appendices expand upon study methods and include the Anchorage Wildlife Plan, which was influenced by study results.
Keywords: forestry; recreation; cognitive therapy; sociology; public administration; cognitive psychology